Application of failure mode and effect analysis in an assisted reproduction technology laboratory. Issue 2 (August 2016) - Intra, Giulia; Alteri, Alessandra; Corti, Laura; Rabellotti, Elisa; Papaleo, Enrico; Restelli, Liliana; Biondo, Stefania; Garancini, Maria Paola; Candiani, Massimo; Viganò, Paola
Abstract: Assisted reproduction technology laboratories have a very high degree of complexity. Mismatches of gametes or embryos can occur, with catastrophic consequences for patients. To minimize the risk of error, a multi-institutional working group applied failure mode and effects analysis (FMEA) to each critical activity/step as a method of risk assessment. This analysis led to the identification of the potential failure modes, together with their causes and effects, using the risk priority number (RPN) scoring system. In total, 11 individual steps and 68 different potential failure modes were identified. The highest ranked failure modes, with an RPN score of 25, encompassed 17 failures and pertained to "patient mismatch" and "biological sample mismatch". The maximum reduction in risk, with RPN reduced from 25 to 5, was mostly related to the introduction of witnessing. The critical failure modes in sample processing were improved by 50% in the RPN by focusing on staff training. Three indicators of FMEA success, based on technical skill, competence and traceability, have been evaluated after FMEA implementation. Witnessing by a second human operator should be introduced in the laboratory to avoid sample mix-ups. These findings confirm that FMEA can effectively reduce errors in assisted reproduction technology laboratories.